Intracellular pH sensing and targeted imaging of lysosome by a galactosyl naphthalimide-piperazine probe. (October 2016) - Fu, Youxin; Zhang, Junji; Wang, Huan; Chen, Jia-Li; Zhao, Ping; Chen, Guo-Rong; He, Xiao-Peng
Abstract: A series of galactosyl naphthalimide-piperazine derivatives have been synthesized as intracellular pH and lysosome-targeting imaging probes for live human hepatoma cells. The probes show good sensitivity in both aqueous buffer and intracellular environments. Incorporation of the galactose moiety with the pH probes facilitates their specific endocytosis and, thus targeted trafficking to lysosome, by the asialoglycoprotein receptor of human hepatoma cells. The acidic intracellular pH of live human hepatoma cells gives rise to a fluorescence "turn-on" signal of the probes probably via a modulation of the photo-induced electron transfer (PET) mechanism. Additionally, galactosylation of the probes enhances their selective accumulation in lysosome and decreases the cytotoxicity. Graphical abstract: A series of galactosyl naphthalimide-piperazine pH probes were designed and synthesized. The designed probes were applied in intracellular pH sensing and targeted fluorogenic imaging of lysosome with minimum cytotoxicity. Highlights: Galactosyl naphthalimide-piperazine based pH fluorescence probes. Intracellular pH sensing and subcellular organelle-targeted imaging. Specific recognition by asialoglycoprotein receptor. Targeted imaging of lysosome organelles in live Hep-G2 cells. Minimal cytotoxicity for the targeted intracellular fluorogenic imaging.